Levonorgestrel-releasing IUD versus copper IUD in control of dysmenorrhea, satisfaction and quality of life in women using IUD - Seyed Javad Purafzali Firuzabadi; Toktam Tavakolianfar; Mamak Shariat; Fatemeh Ramazanzadeh; Fedieh Hagholahi (Iranian Journal of Reproductive Medicine, 2012)
Background: The levonorgestrel-releasing IUD can help the treatment of dysmenorrhea by reducing the synthesis of endometrial prostaglandins as a conventional treatment. Objective: This study was performed to assess the frequency of dysmenorrhea, satisfaction and quality of life in women using Mirena IUDs as compared to those using copper IUDs.Materials and Methods: This double-blind randomized clinical trial was performed between 2006 and 2007 on 160 women aged between 20 to 35 years who attended Shahid Ayat Health Center of Tehran, and they were clients using IUDs for contraception. 80 individuals in group A received Mirena IUD and 80 individuals in group B received copper (380-A) IUD. Demographic data, assessment of dysmenorrhea, and follow-up 1, 3 and 6 months after IUD replacement were recorded in questionnaires designed for this purpose. To assess the quality of life, SF36 questionnaire was answered by the attending groups, and to assess satisfaction, a test with 3 questions was answered by clients. Results: Dysmenorrhea significantly was decreased in both groups six months after IUD insertion as compared to the first month (p<0.001). However, statistically, Mirena reduced dysmenorrhea faster and earlier compared to cupper IUD (p<0.003). There isn’t any significant difference between these two groups in satisfaction and quality of life outcomes. Conclusion: There is no difference between these two groups in terms of the satisfaction and quality of life, therefor the usage of Mirena IUD is not a preferred contraception method.